2006
DOI: 10.1203/01.pdr.0000205477.70391.3e
|View full text |Cite
|
Sign up to set email alerts
|

Lactacidemia in Intrauterine Growth Restricted (IUGR) Pregnancies: Relationship to Clinical Severity, Oxygenation and Placental Weight

Abstract: ABSTRACT:The aim of the study was to evaluate the impact of clinical severity and placental weight upon fetal lactacidemia in intrauterine growth restricted (IUGR) pregnancies. Seventy pregnancies complicated by IUGR were compared with 70 normal (appropriate for gestational age, AGA) pregnancies at the time of elective cesarean section. IUGR pregnancies were divided according to clinical severity in three groups: Group 1 had normal fetal heart rate (FHR) and normal pulsatility index of the umbilical artery (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…While the net lactate flux data ostensibly demonstrates a switch from fetal consumption at low altitude to fetal production at high altitude, the wide range of plasma lactate values means that neither flux is significantly different from zero. Interestingly however, the inverse correlation between umbilical arterial lactate and O 2 content reflects the same relationship observed by Marconi et al in IUGR pregnancies [63].…”
Section: Discussionsupporting
confidence: 85%
“…While the net lactate flux data ostensibly demonstrates a switch from fetal consumption at low altitude to fetal production at high altitude, the wide range of plasma lactate values means that neither flux is significantly different from zero. Interestingly however, the inverse correlation between umbilical arterial lactate and O 2 content reflects the same relationship observed by Marconi et al in IUGR pregnancies [63].…”
Section: Discussionsupporting
confidence: 85%
“…This study of AA uptake and utilization by growth-restricted fetal lamb helps in interpreting data related to human FGR. Clinical studies of FGR pregnancies have shown relationships between placental weight and fetal weight similar to those shown in Figure 1 (18). A significant relationship of placental weight and fetal oxygenation in human FGR has also been demonstrated (8).…”
Section: Pediatric Research 609mentioning
confidence: 62%
“…Additionally, studies have suggested that the ratio of fetal to placental weight is a better marker of placental efficiency, because it represents the amount of fetus produced for each gram of placenta. The ratio MATERNAL OBESITY AND PLACENTAL WNT SIGNALING has been evaluated by several studies, in which the researchers have concluded that a large placenta, when accompanied by a smaller fetus, is associated with IUGR as well as SGA offspring, gestational diabetes, and possible risks of late-onset diseases [7,[62][63][64]. In the present study, we found that placental weight was not affected by maternal weight but that the fetal weight:placental weight ratio was decreased in obese dams, indicating that despite being the same size as those of lean dams, the placentas of these obese dams were not able to support proper fetal development.…”
Section: Strakovsky and Panmentioning
confidence: 99%